Para-Social Interaction and Trust in Live-Streaming Sellers - Thoai Diem Phuong Mai; Anh Tho To; Thi Hong Minh Trinh; Thi Thoa Nguyen; Thi Thanh Trang Le (Emerging Science Journal, 2023)
Live streaming is one of the modern methods that allows sellers to create, transmit, or broadcast some content on the internet in real-time, and it has been used by many small individual merchants. Understanding how live streaming contributes to online consumption is becoming increasingly important in social commerce as the live-streaming industry has grown more and more popular. However, the number of studies on live streaming is still quite limited in Vietnam. Therefore, this research will look at the mechanism that enables live streaming to boost customer trust in streamers. Using PLS-SEM on a sample of 360 respondents who viewed selling live streams on social network sites in Vietnam, we discovered that other members' endorsement, value similarity, hedonic value, and utilitarian value contribute to good para-social interaction. Next, utilitarian and hedonic values, streamer product expertise, and para-social interaction all positively affect trust in the streamers. The findings could help live-streaming sellers better understand their social interactions with viewers, resulting in increased customer trust. Doi: 10.28991/ESJ-2023-07-03-06 Full Text: PDF